Lithobius (Ezembius) tetraspinus, a new species of centipede from northwest China (Lithobiomorpha, Lithobiidae) - Sujian Pei; Yanmin Lu; Haipeng Liu; Xiaojie Hou; Huiqin Ma (ZooKeys, 2018)
Lithobius (Ezembius) tetraspinus sp. n. (Lithobiomorpha: Lithobiidae), recently discovered from Hami City, Xinjiang Autonomous Region, NW China, is described. Morphologically this species resembles L. (E.) sibiricus, Gersfeldt, 1858, but is distinguishable by a different coxal pore formula, absence of accessory spurs on leg 15, morphology of the second article of the female gonopod, and legs 14 plectrotaxy. A table of the main morphological characters of Chinese Lithobius (Ezembius) species is presented.